Engaging Consumers in At-Home Water Conservation: A Guide for Extension - Caroline G. Roper; Alexa J. Lamm (EDIS)
With a growing urban population and increased demands on water for recreational and agricultural purposes, Florida will have to identify a solution to its water quality and quantity issues. Although all Florida residents will play a part in conserving water in the future, the ability of Extension faculty to work with consumers and encourage new water conservation behaviors at home will be vital. This 4-page fact sheet provides information to Extension faculty about the water conservation behaviors in which Florida residents currently engage, water conservation product ownership, and public interest in water-related topics. Written by Caroline G. Roper and Alexa J. Lamm, and published by the UF Department of Agricultural Education and Communication, September 2014.